Design of social housing modules applying ecological fibrablock for housing improvement in an AA.HH. in Pisco, Peru (LACCEI, 2024)
The objective of this research is to carry out the design of social housing modules using ecological fibrablock that allow to correct the habitable need of the inhabitants of an AA.HH. of Pisco, this problem arises from the need for social housing and to reduce the negative environmental impact of construction materials worldwide. That is why ecological panels emerge as a viable alternative for the construction of social housing modules. Likewise, tables and graphs were obtained with the main characteristics and foundations that are part of the analysis of the research that is shown from the Methodology to the Result. Compression tests were carried out on the ecological fibrablock samples to determine their use in the design of the social housing modules Subsequently, the structural, architectural, sanitary and electrical installation plans were prepared. Finally, we can conclude that the results of the compression fractures of the molds were favorable to proceed with the design of the ecological panels. Therefore, the present investigation seeks to cause a positive impact on the environment and contribute to society, through construction, which allows positioning the product to achieve the necessary confidence and include it in the construction of social housing.